Balanced activation of coagulation and fibrinolysis after a 2-h triathlon - Bärtsch, Peter; Welsch, Bärbel; Albert, Michael; Friedmann-Bette, Birgit; Levi, Marcel; Kruithof, Egbert K. O. (Medicine and science in sports and exercise, 1995)
To examine whether exercise-induced thrombin formation is accompanied by increased in vivo plasmin formation, we measured molecular markers and neoantigens of the hemostatic system in 10 male subjects (mean 29 yr, range 19-38) before, immediately after, and 2, 8, and 21 h after a triathlon lasting 128-163 min. Thrombin-antithrombin (TAT) complexes, fibrinopeptide A (FPA), and tissue plasminogen activator (t-PA) antigen were maximally increased immediately after exercise and decreased thereafter rapidly. Prothrombin fragment 1+2 (PTF1+2), fibrin degradation products (FbDP) and plasmin-antiplasmin (PAP) complexes rose to a similar extent 0 and 2 h after exercise and decreased thereafter. The maximal levels of PTF1 + 2, TAT, FPA, and FbDP were 1.5-, 2.1-, 1.8-, and 1.9-fold above baseline values, respectively, while t-PA antigen and PAP rose 9.9− and 10.6-fold above baseline, respectively. This investigation shows that strenuous prolonged exercise leads to a moderate activation of blood coagulation resulting in thrombin and fibrin formation which is accompanied by a greatly enhanced plasmin generation. It is concluded that the hemostatic system of healthy individuals is well kept in balance when stimulated by prolonged strenuous exercise.